The intention to adopt artificial intelligence for software testing by organisations in Klang Valley to achieve sustainable business performance - Khairuddin, Irni Eliana; Apandi, Noorizzati; Ahmad Uzir, Nora’ayu (Faculty of Information Management, 2025)
This study investigates factors influencing the intention to adopt Artificial Intelligence (AI) for software testing among organisations in Klang Valley, Malaysia. As software grows more complex, traditional testing struggles to keep up, increasing interest in AI. Despite its benefits like better defect detection and faster releases, adoption remains limited. Using the Technology-Organisation-Environment (TOE) framework, this study examines the effects of technological, organisational, and environmental readiness. A survey of 219 software testers was analyzed using Structural Equation Modelling (SEM) via SmartPLS. Results show that organisational and environmental readiness strongly influences AI adoption, while technological readiness has a moderate effect. The findings provide useful insights for improving software testing and supporting sustainable business performance.